Characterization of two homeodomain transcription factors with critical but distinct roles in virulence in the vascular pathogen Verticillium dahliae. (17th October 2017) - Sarmiento‐Villamil, Jorge L.; Prieto, Pilar; Klosterman, Steven J.; García‐Pedrajas, María D.
Summary: Vascular wilt caused by Verticillium dahliae is a destructive disease that represents a chronic economic problem for crop production worldwide. In this work, we characterized two new regulators of pathogenicity in this species. Vph1 (VDAG_06555) was identified in a candidate gene approach as a putative homologue of the transcription factor Ste12. Vhb1 (VDAG_08786), identified in a forward genetics approach, is similar to the homeobox transcription factor Htf1, reported as a regulator of conidiogenesis in several fungi. Deletion of vph1 did not affect vegetative growth, whereas deletion of vhb1 greatly reduced sporulation rates in liquid medium. Both mutants failed to induce Verticillium wilt symptoms. However, unlike Δ vph1, Δ vhb1 could be re‐isolated from the vascular system of some asymptomatic plants. Confocal microscopy further indicated that Δ vph1 and Δvhb1 differed in their behaviour in planta ; Δ vph1 could not penetrate the root cortex, whereas Δ vhb1 was impaired in its ability to colonize the xylem. In agreement with these observations, only Δ vhb1 could penetrate cellophane paper. On cellophane, wild‐type and Δ vhb1 strains produced numerous short branches with swollen tips, resembling the hyphopodia formed on root surfaces, contrasting with Δ vph1, which generated unbranched long filaments without swollen tips. A microarray analysis showed that these differences in growth were associated with differences in global transcription patterns, and allowed us to identify a large set of novel genes potentially involved in virulence in V. dahliae . Ste12 homologues are known regulators of invasive growth, but Vhb1 is the first putative Htf1 homologue identified with a critical role in virulence.